Quality of life before & after genitourinary fistula repair - Insights from WHOQOL-BREF - Shaikh, Iqra; Mahar, Naveed Ahmed; Piyarali, Shireen; Murli Lal; Hahmi, Altaf (Journal of the Pakistan Medical Association, 2026)
Objective: To compare preoperative and postoperative quality of life in women undergoing genitourinary fistula repair. Method: The quasi-experimental study was conducted at the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi, from January to December 2023, and comprised female patients diagnosed with vesicovaginal fistula secondary to gynaecological and obstetric procedures or trauma. The quality of life was assessed using the brief version of the World Health Organization Quality of Life scale. The participants completed the questionnaire both before the surgical intervention and three months after successful fistula repair. Data was analysed using SPSS 26. Results: There were 30 women with mean age 35.50±8.87 years. Mean quality of life score at baseline was 12.17±5.77 which improved significantly to 96.67±11.86 post-intervention (p=0.0001). Conclusion: Genitourinary fistula repair significantly and positively impacted the patients’ quality of life. Key Words: Genitourinary fistulae, Vesicovaginal fistulae, Ureterovaginal fistulae, O’Connor repair, Robotic-assisted VVF repair, Transvaginal repair, WHOQOL-BREF.